Monitoring Variations in Thermal Curing of Nanoparticle Coatings through Confocal Raman Microscopy and Principal Component Analysis. Issue 13 (13th February 2020) - Samyn, Pieter; Marchal, Wouter; Vandamme, Dries; Adriaensens, Peter; Carleer, Robert
Abstract : For paper coatings with organic nanoparticles of poly(styrene‐ co ‐maleimide), dispersive Raman spectroscopy and confocal Raman microscopy are applied for qualitative and quantitative analyses of the lateral distribution of chemical moieties as a function of different coating grades (degree of imidization) and thermal curing temperatures (120–250 °C). Raman mapping with band intensity ratios, single band intensities, and average spectral intensities illustrates that surface locations with imide moieties are sensitive to the thermal curing temperature due to the reactivity of an amount of ammonolyzed (nonimidized) maleic anhydride, whereas the styrene moieties are not sensitive to the thermal curing. A maximum in imide functionalities at the surface occurs after curing at 135–150 °C depending on the coating grade. The surface coverage of the coating moieties is complementary to the cellulose components, but local variations in specific Raman bands for the latter suggest interactions due to hydrogen bonding. Principal component analysis with two parameters allows for a good quantification of the imide content and surface coverage. Abstract : Raman spectroscopy and chemical imaging by confocal Raman microscopy are applied to detect the variation in chemical moieties at the surface of coated papers as a function of the thermal curing temperature. The combination with principal component analysis allows to derive qualitative and quantitative data on surface coverage and imide content.